From A Liability To An Asset: The American Changing Perspectives About The Role of Algeria In The Region From 1990s To 2021 - Hassina Amrouche, Dr. Youcef BennaaChafya Delali (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract The new global mission of the United States of America after its victory in the Cold War is fighting terrorism - which became more important after the events of September 11, 2001- which made USA constantly doubt about any Islamic country that could be considered a source of radical Islamic fundamentalism that could turn into terrorist groups, as what happened towards Algeria, American policy is based on this misunderstanding with all Islamic countries. This thesis shows how the American perspective on Algeria changed from a source of a terrorist threat in the 1990s to an expert ally assisting in its global mission after 2001. This research also aims to reveal the reasons for this change and the extent of Algeria's contribution to this war. This study deals with an overview of the history of the AmericanAlgerian relationship since the first contact until this sensitive period. It also follows the course of Islamic radicalism from its emergence in Algeria to its hegemony in the Algerian political arena, and what happened after the abolition of democracy in Algeria at the time, and the violent incidents and bloody massacres that followed it against the people. This letter also deals with the Algerian-American relationship after 9/11 and how these terrorist attacks changed the relationship between the two countries from a misunderstanding to political and military cooperation.
Keywords: KEY WORD: Algeria, American, Cooperation, Perspective, Islamic Country, Radicalism.